Uso de recursos estimuladores da aprendizagem significativa no ensino de física - Santos, Ernani dos (Universidade Federal de São Carlos, 2012)
This research deals with resources which lead to significant learning consistent with the needs of modern society and encourages students to develop knowledge in Physics, in order to enable them to interact with the community in a critical and consistent manner towards an intellectual, economic and technological development in a conscious and sustainable way. Therefore, we studied teaching methods based on constructivism and meaningful learning, coupled with application of resources to explore the school environment and technologies related to education and practical application of Science in low cost experiments; in Science Museums and Thematic Parks; aiming to recover the values of the school and offer a new perspective on education for teachers and students, who pressed for mutual participation in the teaching-learning and highlight its importance in the progress of the nation.
Keywords: Física - estudo e ensino; significativa; Exploração do ambiente escolar; Tecnologias da informação; Objetos de aprendizagem; Atividades prático-experimentais; Ambientes não formais; Meaningful learning; Exploration of the school environment; Information technology; Learning objects; Practical and experimental activities; Non-formal environments; CIENCIAS EXATAS E DA TERRA::FISICA